The Role of Youth and GE-14 in Sabah: Case Study in P.188 Silam - Ramli Dollah; Nordin Sakke; Wan Shawaluddin Wan Hassan; Marja Azlim Omar; Adi Jafar (2018)
The youths are an essential group of voters in Malaysian politics. With the rising number of youths, representing almost half of registered voters in Malaysia, their roles are pertinent as they were able to determine the result of the election. This is because these groups of young peoples are susceptible to the changes that are taking place in their surroundings and they are also very critical of the government's policies that may not serve their interests. Based on the study carried out on the role of youth during the 14th General Election (GE-14) in the Parliament (P.188) Silam and three other state seats (N. 51 Kunak, N. 50 Lahad Datu and N. 49 Tungku), it was found that the protest among youths in these Parliament constituents was due to the failure of the previous government, Barisan Nasional (BN) in implementing policies and programs that benefitted the youths. They translated their protests in the form of casting their votes to choose the opposition party, i.e. Parti Warisan Sabah (PWS) to come into power. Recognizing the importance of the youths in determining the survival of the ruling party, this article concludes that the current government at the state and national level needs to give serious attention to the issue of the marginalisation among the youths. Therefore, more efforts should be undertaken to reach out and to engage the youths on a regular basis as opposed to the previous practices of only approaching them before and during election season.